METAFORA DALAM RAGAM BAHASA PUISI (PENDEKATAN TEORI COGNITIF LINGUISTIK) - Rizka Hayati (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2016)
Metaphor is something that is commonly used in poem. The use of metaphor in poem can give the poem a deeper meaning and understanding. Thus, metaphor in poem becomes phenomena which is interesting to be analyzed. From the background above, the writer is interested in analyzing the use of metaphor in poem. The objective of this study is to find out metaphors in poems and interpret the meaning. This study analyzes the meaning of metaphor by using cognitive linguistics approach. The object of the study is poem “Aku” and “Karawang Bekasi” by Chairil Anwar and "Bulu Matamu: Padang Ilalang" by Joko Pinurbo. The technique that the writer used to analyze the data were identifying, associating, interpreting, and concluding. The result showed that there some metaphors found in the poems. The metaphors were used in “Aku” related to the condition of someone who struggle in his life. These metaphors described the condition of someone who always struggle for his better life although he had a lot of problems in his life. The metaphors in “Kerawang Bekasi” related to the effort of someone who had never gave up to get freedom for his country although he had to give his life (died) for his country. This poem described the spirit of nationality. The last is the use of metaphor in “Bulu Matamu: Padang Ilalang”. The metaphors used in the poem represented the beauty of someone’s eyes. The metaphors were used to make the poems more beautiful and interesting. It also gives the meaning beyond the word itself.